Analisis Penerapan PSAK 409 Tentang Akuntansi Zakat, Infak dan Sedekah pada BAZNAS Kabupaten Tangerang - Fitria Nuraini; Iwan Setiawan; Lina Yulianti (Institut Agama Islam Negeri Ponorogo, 2025)
The objective of this study is threefold: firstly, to ascertain and analyse the procedures for implementing zakat, infaq, and sadaqah accounting at BAZNAS Tangerang Regency; secondly, to evaluate the suitability of implementing zakat, infaq, and sadaqah accounting based on PSAK 409 at BAZNAS Tangerang Regency; and thirdly, to propose strategies for implementing PSAK 409 at BAZNAS Tangerang Regency. PSAK 409 is an accounting standard that regulates financial reporting for the management of zakat, infaq, and sadaqah. The research method employed is a descriptive method that utilises a qualitative approach. The type of data utilised is qualitative, with the data sources comprising primary and secondary data. It can be concluded that the procedures for implementing zakat, infaq and sadaqah accounting have used excel, SIMBA and SIMAMBA; the suitability of implementing PSAK 409 at BAZNAS Tangerang Regency is not yet fully in accordance with the recognition, measurement, presentation and disclosure; and the strategy for implementing PSAK 409 at BAZNAS Tangerang Regency through SWOT analysis includes utilising the accounting system, optimising the structure of an integrated institution, improving the quality of resources, utilising government regulations, strengthening collaboration with external auditors and quickly adapting to regulatory changes.